Not leaving the conversation behind: approaching a decade of teaching reflective journal writing at a liberal arts college. Issue 5 (3rd September 2017) - Power, John Brian
Abstract: Approaching a milestone in his teaching career, the author set out to document his observations on mentoring reflective journal writing with the aims of capturing his own learning journey and providing insights into future practice. Such recollections of teachers' learning from experience in the higher education context have been subject to relatively little investigation. Some key points emerge: reflective journal writing is considered fundamental to advancing the core principles of the liberal arts tradition, specifically by allowing students to articulate their understanding of the more abstract concepts fundamental to undergraduate learning. Over time, mentoring of journal writing can provide rich individual and collective portraits of learner development. At the heart of this discussion is the belief that the 'art' of mentoring good journal writing lies in taking cues from the students, and acknowledging and incorporating their insights and first-hand experience of the process into classroom instruction. It is hoped that these reflections may be beneficial for teachers beginning or continuing their reflective journal mentoring.